Are fewer cases of diabetes mellitus diagnosed in the months after SARS-CoV-2 infection? A population-level view in the EHR-based RECOVER program. Issue 1 (8th March 2023) - Reddy, Neha V.; Yeh, Hsin-Chieh; Tronieri, Jena S.; Stürmer, Til; Buse, John B.; Reusch, Jane E.; Johnson, Steven G.; Wong, Rachel; Moffitt, Richard; Wilkins, Kenneth J.; Harper, Jeremy; Bramante, Carolyn T.
Abstract: Long-term sequelae of severe acute respiratory coronavirus-2 (SARS-CoV-2) infection may include increased incidence of diabetes. Here we describe the temporal relationship between new type 2 diabetes and SARS-CoV-2 infection in a nationwide database. We found that while the proportion of newly diagnosed type 2 diabetes increased during the acute period of SARS-CoV-2 infection, the mean proportion of new diabetes cases in the 6 months post-infection was about 83% lower than the 6 months preinfection. These results underscore the need for further investigation to understand the timing of new diabetes after COVID-19, etiology, screening, and treatment strategies.